Alkene 1, 2‐Difunctionalization by Radical Alkenyl Migration. (14th December 2017) - Tang, Xinjun; Studer, Armido
Abstract: Transition‐metal‐free radical α‐perfluoroalkylation with the accompanying vicinal β‐alkenylation of unactivated alkenes is presented. These radical cascades proceed by means of 1, 4‐ or 1, 5‐alkenyl migration by electron catalysis on readily accessed allylic alcohols. The reactions comprise a regioselective perfluoroalkyl radical addition with subsequent alkenyl migration and concomitant deprotonation to generate a ketyl radical anion that sustains the chain as a single‐electron‐transfer reducing reagent.